The Killing of bin Laden and the Undermining of Public Health - Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2012)
The military raid in Abbottabad, Pakistan, that resulted in the killing of Osama bin Laden was preceded by a fake childhood immunization campaign meant to collect DNA samples for confirming the bin Laden family’s presence. This use of a public health activity under false pretences undermines the validity and effectiveness of international public health endeavours, and may put workers in danger. It is time for agencies and governments to declare that health and development programs will no longer be used as cover for violent or subversive adventures.